PREDICTION OF LOCALIZED INFLAMMATORY PERIODONTAL TISSUE DISEASES IN YOUNG PERSONS - O.V. Kholodnyak (Ukrainian Medical Stomatological Academy, 2015)
Periodontal diseases are among the diseases that are known from ancient times. Their prevalence has increased dramatically with the progress of civilization. At present the problem of prevention and treatment of periodontal diseases is presented in many domestic and foreign studies. Therefore, the strategy of prevention of these diseases should be based on the concept of risk factors. However, the issue of forecasting, prevention and treatment of periodontal tissue diseases by the action of local damaging factors has not been sufficiently studied. The aim of the research is to detect the predictive values of clinical, physical, chemical and functional studies in the development of localized inflammatory periodontal disease in young adults. Materials and methods. The analysis of the prognostic value of clinical, physical, chemical and functional parameters in localized forms of periodontal disease in 76 young patients (34 - with limited chronic catarrhal gingivitis; 42 - with chronic localized periodontitis, and initial severity) was conducted by mathematical processing of the values with "Wald sequential analysis" and Bayes theorem. Results. Statistical analysis of parametric and non-parametric indicators of traumatic local and individual factors against the risk of localized periodontal disease (gingivitis, periodontitis) in young adults enabled us to compose a table with prognostic value of quantitative criteria of evidence (prognostic factors). The most informative local 5 and 9 individual high risk factors of limited chronic catarrhal gingivitis have been established which enables the prediction of the disease. Regarding prognosis of limited chronic catarrhal gingivitis, the prognostic factors of local traumatic factor in the degree of importance were: deficiently shaped teeth in the treatment of caries → cervical site availability of untreated carious process → orthodontic appliances → dental plaque. The high degree of relevance have individual risk factors for disease, gum recession (≥1 mm), Green-Vermilion index (0.7-1.6 points), Silness-Loe index (>1 <2 points), the rate of salivation (<0 6 ml / min.), the pH of the oral and gingival fluid (≤6.5). The deepening of the pathological process in periodontal tissues is accompanied by increased local and individual prognostic criteria of disease in young adults. The high proportion of local 7 and 12 individual risk factors for chronic localized periodontitis is of primary importance for prognosis. The most important diagnostic features for predicting development of chronic localized periodontitis of initial severity are the degree of significance, poorly executed restoration in the treatment of dental caries in cervical area → dental plaque → traumatic occlusion. The high individual prognostic criteria are epithelial attachment loss, gingival recession (≥1 mm), depth of periodontal pockets (>2 mm), Green-Vermilion index (1.7-2.5 points) Silness-Loe index (≥2 points), the Ri index (1-2 points), the rate of salivation (<0.6 ml / min.), the pH of the oral and gingival fluid (≤6.5). Conclusion. Based on the results of the study and given the significance of the signs listed above, one can conduct individual prognosis of localized periodontal lesions in young people, defining a set of parameters of traumatic local factors and individual risk of disease.